Electronic and optical properties of chloropicrin adsorbed ZnS nanotubes: first principle analysis - Prakash Yadav; Boddepalli SanthiBhushan; Anurag Srivastava (Beilstein Journal of Nanotechnology, 2025)
Zinc sulfide nanotubes have garnered significant attention as potential candidates for chemical sensing applications owing to their exceptional structural, electronic, and optical properties. In this study, we employed density functional theory (DFT) to explore the sensing capabilities of a ZnS (3,3) nanotube (ZnS NT) for detecting chloropicrin (CP, CCl3NO2), a highly toxic gas. To elucidate the sensing mechanism, we systematically analyze the adsorption configurations, Mulliken charge transfer, band structure, density of states, optical absorption, and optical conductivity of the ZnS NT-CP system. Our findings reveal that the interaction between CP and ZnS NT induces notable changes in the electronic and optical properties of the nanotube, including a substantial bandgap reduction of up to ≈40% for the specific orientation A. The adsorption energy ranges from −0.389 to −0.657 eV, indicating weak physisorption. The Mulliken charge transfer varies between 0.06e and 0.109e, confirming effective but nondestructive interaction. A favorable recovery time of ≈3.533 μs at room temperature, along with a significant red shift in the absorption spectra and optical conductivity peaks, highlight the potential of ZnS NT for designing sensitive and reusable CP gas sensors.